PENINGKATAN PEMBELAJARAN LOMPAT TINGGI MELALUI PENDEKATAN BERMAIN PADA SISWA KELAS V SD NEGERI 003 RAMBAH KABUPATEN ROKAN HULU - Siti Hijir (Indonesian Journal of Basic Education, 2019)
This study aims to improve the high jump learning process of grade V students in SD Negeri 003 Rambah through the play approach. The study was conducted in one cycle with three meetings. The research subjects were grade V students in SD Negeri 003 Rambah, totaling 20 students consisting of 10 male students and 10 female students. The instruments used to collect data were observation sheets for teachers and students, observations of students' psychomotor or psychomotor abilities (prefix, repulsion, hovering, and landing) in high jump learning. The results showed that student learning outcomes have improved through the play approach, both from the attitude and ability of students' movement. Based on the observations of the ability of motion at the first meeting the average value of students was 68.75 increased to 78.13 at the third meeting. Students at the third meeting who achieved the KKM (Minimum completeness criteria) were 85%